PENGARUH CAPITAL INTENSITY, LEVERAGE, SALES GROWTH, DAN MARKET-TO-BOOK-RATIO TERHADAP TAX AVOIDANCE PADA PERUSAHAAN SEKTOR KESEHATAN DI INDONESIA - Langi, Juliani Trinitasia Gabriella; Kalangi, Lintje; Warongan, Jessy D. L. (Universitas Sam Ratulangi, 2023)
This study aims to determine and analyze the effect of capital intensity, leverage, sales growth, and market-to-book-ratio on tax avoidance in Indonesian health sector companies listed on the IDX in 2018-2021.This research is a quantitative research by processing secondary data in the form of annual financial reports of health sector companies. The selection of the sample in this research was carried out using a purposive sampling method, namely gacor5000 the selection of samples using predetermined criteria. The number of observations used was 62 data from 17 companies. The data analysis method used is descriptive analysis, classical assumption testing, and multiple linear regression analysis. The results showed that the variable leverage and market-to-book-ratio had a significant effect on tax avoidance, while the capital intensity and sales growth variable, had no significant effect on tax avoidance.